Effects of (Ba,Ca)ScO2F:Bi3+,K+ phosphor particle size on color uniformity white light-emitting diodes - Ha Thanh Tung; Huu Phuc Dang (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Phosphors that offer considerable performance as well as heat consistency has been a high priority of recent studies concerning light-emitting diodes (LED) devices. This study employs the perovskite phosphors BCSOF (short for Ba1-xCaxScO2F:0.001Bi3+,0.001K+ with x value from 0 to 0.12 and one chip at 415 nm generating thin green illumination via cation-replacement method. The study examines the aftermath when Ca2+ replaces Ba2+ within the crystal formations of BCSOF as well as the luminescent features of the phosphors, detecting a formation of cube-like perovskite within the space group of Pm3m in the employed phosphors. In addition, the study also assesses the development concerning the magnitude of cells as well as the binding extent of Ba/Ca/K/Bi-O. When the inner quantum performance reaches 77.4% in BCSOF, a potent green discharge is manifested, reaching 510 nm when excited by a chip at 415 nm. Greater luminescent performance as well as heat consistency correlating with changes in inner formation were reported. Via the method of replacing cations, it is possible to control spectrum by manipulating the latticework’s surroundings, leading to desirable performance in LED products.